2007
DOI: 10.1177/0952076707071502
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking ‘The Public’ in Troubled Times

Abstract: This article begins with contemporary concerns about the demise of public institutions and public values. New strategies of governance across Europe and beyond make any clear delineation of ‘the public’ and the public sphere highly problematic. The modernization of welfare states involves a shift of powers from state to market, but also a shift of responsibility from public to personal domains. The liberal values associated with the traditional public sphere seem illequipped to address questions of social dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Frederickson (1997) and Goldsmith & Eggers (2004) suggested that governance has become a virtual synonym for public management and public administration. Newman (2007) said that it is perhaps better to regard governance as an umbrella or portmanteau concept.…”
Section: Governance Theory and Its Applicability In Chinamentioning
confidence: 99%
“…Frederickson (1997) and Goldsmith & Eggers (2004) suggested that governance has become a virtual synonym for public management and public administration. Newman (2007) said that it is perhaps better to regard governance as an umbrella or portmanteau concept.…”
Section: Governance Theory and Its Applicability In Chinamentioning
confidence: 99%
“…These ideas drew support from the American political scientist Mark Moore’s notion of “public value.” Moore’s book, which was taken up by Mulgan while head of the Prime Minister’s Strategy Unit, was a manifesto for transforming public management away from centralized bureaucratic structures toward more flexible, decentralized and responsive relationships between “coproduce[rs]” (Moore 1995, 117–118; Wilsdon et al 2005, 28; cf. Newman 2007, 41). In Moore’s view, public sector management should be about finding “ways to engage loose networks of professions, interest groups, political associations, and the media in efforts to coproduce the managers’ goals” (Moore 1995, 118).…”
Section: Governing Through Culturementioning
confidence: 99%
“…The analysis highlights the significance of differences in perspective between actors and their implications for policy and practice. The narratives serve to illuminate not only the particular case of faith engagement but also the more general character of British urban governance as it takes on an increasingly "decentered" form (Bevir and Rhodes, 2001), in which boundaries between the public, private, and personal become ever more blurred (Newman 2005(Newman , 2007.…”
mentioning
confidence: 99%